Trends of Large for Gestational Age and Macrosomia and Their Mediating Effect on the Association Between Diabetes Mellitus and Obstetric Hemorrhage - Peiran Chen; Yi Mu; Yanxia Xie; Yanping Wang; Zheng Liu; Mingrong Li; Juan Liang; Jun Zhu (Maternal and Child Nutrition, 2025)
ABSTRACT This study aimed to determine the prevalence of large for gestational age (LGA) and macrosomia in China from 2012 to 2021 and explore if LGA and macrosomia mediate the relationship between diabetes mellitus in pregnancy (DIP) and obstetric haemorrhage. The overall annual change rate (ACR) was calculated, and stratification analysis was performed. Mediation analysis assessed the influence of LGA and macrosomia in the association between DIP and obstetric haemorrhage. The nationwide prevalence of LGA and macrosomia was 15.8% and 6.8%, respectively. The ACR for LGA was 0.71% (95% CI, 0.66%–0.76%); pre‐2016, −0.44% (95% CI, −0.63% to −0.25%); post‐2016, −0.29% (95% CI, −0.39% to −0.19%). The ACR for macrosomia was −1.17% (95% CI, −1.24% to −1.09%); pre‐2016, −0.73% (95% CI, −1.03% to −0.43%); post‐2016, −2.42% (95% CI, −2.59% to −2.26%). In western and rural area, the ACR for LGA was 1.94% (95% CI, 1.84%–2.05%) and 1.81% (95% CI, 1.73%–1.89%), and LGA was increasing among these women in the post‐2016 period. About 7.0% of pregnant women had DIP, and the LGA and macrosomia prevalences among women with DIP were 23.7% and 10.0%, respectively. In the mediation analysis, the total excess risk associated with DIP on obstetric haemorrhage was approximately 0.21 and the proportion mediated by LGA and macrosomia was 12.10% and 11.81%, respectively. In rural areas, the proportion mediated by LGA and macrosomia was amplified to 18.34% and 16.40%. Macrosomia rates declined steadily, but LGA rates increased slightly in disadvantaged areas. LGA and macrosomia mediated the association between DIP and obstetric haemorrhage, and the mediating effect intensified in rural regions. Addressing LGA warrants management for at‐risk fetuses.